(untitled) (Journal of Atomic and Molecular Sciences, 2010)
Adsorption studies of Cs^+, Tl^+, Sr^2+ and Co^2+ on activated carbons from aqueous solutions are reported. The carbon samples were characterized using different techniques. The chemical nature of the surface of the activated carbon was studied. Optimal conditions for adsorption of the metal ions have been identified. The comparative study for the metal ions was also considered in the presence of different anions. The data suggest the possible use of activated carbons for preconcentration and separation of some cations.